Consumption of dietary nuts in midlife and risk of cognitive impairment in late-life: the Singapore Chinese Health Study. (18th December 2020) - Jiang, Yi-Wen; Sheng, Li-Ting; Feng, Lei; Pan, An; Koh, Woon-Puay
Abstract: Background: evidence from prospective studies investigating the association between consumption of nuts in midlife and risk of cognitive impairment in late life is limited. Methods: this study analysed data from 16, 737 participants in a population-based cohort, the Singapore Chinese Health Study. Intake of nuts was assessed using a validated food-frequency questionnaire at baseline (1993–1998), when participants were 45–74 years old (mean age = 53.5 years). Cognitive function was tested using the Singapore modified Mini-Mental State Examination during the third follow-up visit (2014–2016), when participants were 61–96 years old (mean age = 73.2 years). Cognitive impairment was defined using education-specific cut-off points. Logistic regression models were used to estimate the odds ratio (OR) and the 95% confidence interval (CI) for the association between intake and risk of cognitive impairment. Results: cognitive impairment was identified in 2, 397 (14.3%) participants. Compared with those who consumed <1 serving/month of nuts, participants who consumed 1–3 servings/month, 1 serving/week and ≥2 servings/week had 12% (95% CI 2–20%), 19% (95% CI 4–31%) and 21% (2–36%) lower risk of cognitive impairment, respectively ( P -trend = 0.01). Further adjustment for intake of unsaturated fatty acids attenuated the association to non-significance. Mediation analysis showed that the 50.8% of the association between nuts and risk of cognitive impairment was mediated by the intake of total unsaturated fatty acids ( P < 0.001). Conclusion: higher intake of nuts in midlife was related to a lower risk of cognitive impairment in late life, which was partly mediated by unsaturated fatty acids.